Clinical management of intra-pulp canal broken endodontic files in primary teeth : literature review = Manejo clínico de las limas endodónticas fracturadas dentro del conducto pulpar en dientes primarios : revisión de la literatura - Garrocho Rangel, Arturo 1961-
Fracture of an endodontic file inside a primary root canal is a rare but critical complication during the pulpectomy treatment, because the mechanical obstruction impedes the optimal cleaning and obturation of the pulp canal, compromising seriously the clinical outcome. This accidental event is mainly associated with over-use and excessive torque of intracanal files. Most clinicians opt to proceed with the extraction of the affected tooth followed by a space maintainer placement. Other practitioners attempt the non-surgical retrieval of the separated fragment through available proven techniques in permanent teeth; however, these methods may involve significant damage to the tooth and surround tissues. On the other hand, preservation of the metallic fragment might affect the treatment prognosis and interfere with the physiological root resorption.